2013
DOI: 10.1074/jbc.m112.425728
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pilus Proteins in Adherence and Invasion of Streptococcus agalactiae to the Lung and Cervical Epithelial Cells

Abstract: Background:Pili have been shown to play a key role in the attachment. Results: Pilus proteins anti-SAN1518, GBS80, and GBS67 inhibited the adherence and invasion of GBS to the lung and cervical epithelial cells. Conclusion: Pilus protein contributes to the initial attachment and invasion of GBS. Significance: Pilus protein-based vaccine formulation can also be tested against GBS serotypes of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Several studies have previously reported that unique GBS strains differ in their abilities to attach to and invade host cells (11)(12)(13)(14)(15)(16). However, the strains tested in the prior studies were chosen based on serotype, a phenotypic characterization dictated by capsular polysaccharide genes, rather than on a genotypic characterization, such as ST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously reported that unique GBS strains differ in their abilities to attach to and invade host cells (11)(12)(13)(14)(15)(16). However, the strains tested in the prior studies were chosen based on serotype, a phenotypic characterization dictated by capsular polysaccharide genes, rather than on a genotypic characterization, such as ST.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GBS effectively adheres to and invades epithelial and endothelial cells. Additionally, GBS strains of different serotypes differ in their abilities to associate with host cells (11)(12)(13)(14)(15)(16); however, such studies selected strains on the basis of cps type rather than ST. Because cps is horizontally transferred between strains and there is evidence of capsule switching (17,18), selecting strains based on ST, or genetic backbone, is warranted. Comparing the hypervirulent lineage, ST-17, with other lineages with respect to the ability to attach to and invade host cells will facilitate the identification of factors that play an important role in GBS disease development.…”
mentioning
confidence: 99%
“…It has already been shown that an acidic pH can modulate the expression of a large number of proteins in GBS, including the proteins involved in surface adhesion (43,44). Several proteins have already been reported to be important for ST-17 strain adhesion to solid surfaces or attachment to host cells or extracellular matrix (21,42,45,46). Our data suggest that the contradictory reports about the effects of pH on GBS adherence to epithelial cells (44,(47)(48)(49), like previous reports about the effects of pH on biofilm formation, could be due to the limited number of GBS strains tested and the methods used.…”
Section: Figmentioning
confidence: 99%
“…Pilus proteins have been described as having a key role in S. agalactiae pathogenesis (Maisey et al, 2007;Konto-Ghiorghi et al, 2009) and have been proposed as good vaccine candidates (Sharma et al, 2013). Although the pilus proteins do not belong to the core genome of all 15 strains of S. agalactiae, promising results in development of universal vaccines have been proposed by a combination of immunogenic pilus proteins of three PIs (Margarit et al, 2009).…”
Section: Continued On Next Page Prediction Of Vaccine Targets In Strementioning
confidence: 99%